ANALISIS KUALITAS AIR LAUT TERHADAP KELESTARIAN BUDIDAYA RUMPUT LAUT DI PANTAI NUSA PENIDA, BALI - Sudipa, Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 1 (2024)DO - 10.24843/EJES.2024.v18.i01.p04, 2024)
Seaweed cultivation is one of the economic resources of the Nusa Penida community. This research determines the condition of Nusa Penida's waters to support the existence of seaweed cultivation. This research uses a quantitative approach to the water conditions of Nusa Penida. The results of the pollution index calculation show that the quality of sea water on the coast of Nusa Penida is in good condition and very good for seaweed life in Nusa Penida waters which can be seen from the results of physical, chemical and microbiological parameter tests. Parameters that influence the sea water pollution index are total disolved solids parameters, ammonia and nitrite in Jungutbatu sea water, Nitrite in Toyapakeh sea water, total disolved solids, Ammonia and nitrite in Penida sea water, Nitrite in Buyuk Kutampi sea water, Ammonia and Nitrite in Sampalan sea water, and Nitrite. in Suana sea water. Keywords: Pollution Index; Water Quality; Seaweed; Total Disolved Solids